KORUPSI DALAM PENGALOKASIAN DANA BANTUAN COVID-19 DI KABUPATEN SAMPANG - Nurlaili, Ismahani (PUSAT KAJIAN ANTI KORUPSI FAKULTAS HUKUM UNIVERSITAS JEMBER, 2022)
Corruption in the public service process is not new in Indonesia, especially during the Covid-19 pandemic. The government provides Covid-19 social incentives as an effort to stabilize and restore the community's economy due to the impact of the Covid-19 pandemic, which has decreased income, which has an impact on the welfare of the community. This study uses normative juridical research methods in which it uses the approach of covid-19 social incentives corruption cases in Sampang Regency. The results showed that there was corruption in the Sampang Regency area, there was a misappropriation of the allocation of Covid-19 social incentives funds, causing state losses, in which there was a lot of overlap related to assistance funds both in cash and in the form of basic necessities. Efforts to prevent corruption in public services should be maximized by the active role of all components of both government and society. The government can maximize the performance of the Corruption Eradication Commission (KPK) and impose appropriate laws for perpetrators of corruption and innovate public services by utilizing technological developments, such as by establishing and launching an integrated social assistance Corruption Prevention information system.